Giant Optical Second Harmonic Generation in Two-Dimensional Multiferroics - Wang, Hua; Qian, Xiaofeng (Nano letters, 2017)
Nonlinear optical properties of materials such as second and higher order harmonic generation and electro-optic effect play pivotal roles in lasers, frequency conversion, electro-optic modulators, switches, and so forth. The strength of nonlinear optical responses highly depends on intrinsic crystal symmetry, transition dipole moments, specific optical excitation, and local environment. Using first-principles electronic structure theory, here we predict giant second harmonic generation (SHG) in recently discovered two-dimensional (2D) ferroelectric–ferroelastic multiferroics–group IV monochalcogenides (i.e., GeSe, GeS, SnSe, and SnS). Remarkably, the strength of SHG susceptibility in GeSe and SnSe monolayers is more than 1 order of magnitude higher than that in monolayer MoS2, and 2 orders of magnitude higher than that in monolayer hexagonal BN. Their extraordinary SHG is dominated by the large residual of two opposite intraband contributions in the SHG susceptibility. More importantly, the SHG polarization anisotropy is strongly correlated with the intrinsic ferroelastic and ferroelectric orders in group IV monochalcogenide monolayers. Our present findings provide a microscopic understanding of the large SHG susceptibility in 2D group IV monochalcogenide multiferroics from first-principles theory and open up a variety of new avenues for 2D ferroelectrics, multiferroics, and nonlinear optoelectronics, for example, realizing active electrical/optical/mechanical switching of ferroic orders in 2D multiferroics and in situ ultrafast optical characterization of local atomistic and electronic structures using noncontact noninvasive optical SHG techniques.